Patient Perception of Health Care Services: A Comparative Study - Pai, Rashmi Ananth (Journal of Social and Development Sciences, 2013)
Assessment of patient satisfaction is a measurement that obtains information or ratings from patients about their perception of the services being provided from an organization, hospital, physician, or healthcare provider and plays an increasingly important role toward accountability among health care providers. The present study aimed at comparing the patient’s perception of services being provided in the government and private sectors. 120 patients (60 from each sector) natively from Karnataka, India with knowledge of English participated in this study. Subjects were asked to rate their experiences before, during and after consultation. A checklist to rate the patient satisfaction was developed. The checklist comprised of 11 questions covering the most important domains pertaining to patient satisfaction about the health care services provided. Obtained responses were statistically compared using independent t test. Significant differences in the satisfaction levels of the subjects in the government and the private set ups were seen at p< 0.05 (t=2.921, 118). In government sector patients were better satisfied with certain aspects like the cost factor, information provided about the problem and guidance regarding intervention whereas the patients in the private sector were better satisfied with the orientation to the department, information furnished about the problem, comfort and privacy during the testing procedure.